Lady Gaga and the Sociology of Fame : The Rise of a Pop Star in an Age of Celebrity - Deflem, Mathieu (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2017)
This book investigates the stardom of Lady Gaga within a cultural-sociological framework. Resisting a reductionist perspective of fame as a commodity, Mathieu Deflem offers an empirical examination of the social conditions that informed Lady Gaga's rise to fame. The book delves into topics such as the marketing of Lady Gaga; the legal issues that have dogged her career; the media; her audience; her activism; issues of sex, gender, and sexuality; and Lady Gaga's unique artistry. By training a spotlight on this singular pop icon, Lady Gaga and the Sociology of Fame invites readers to consider the nature of stardom in an age of celebrity.